2018
DOI: 10.1002/srin.201800473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon and Boron on Structure and Properties of Austenitic Stainless Steel Coatings Fabricated by Laser Remanufacturing

Abstract: The coatings are fabricated using austenitic stainless steel powder with various contents of carbon and boron via laser remanufacturing technique. A new synchronous lateral powder feeding device is adopted to avoid surface oxidation of molten pool. The authors find that the strength can be increased but plasticity is decreased of with the rise of boron content due to the formation of lamellar borides phase structures, which are very brittle and have high hardness. In addition, the authors also find that the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Steel for those structures needs to have superior comprehensive properties, such as high strength, low-temperature impact toughness, seawater corrosion resistance, and good field weldability [2]. Studies have shown that a new type of ultra-low carbon bainite (ULCB) steel can meet those requirements of excellent comprehensive properties and more cost-effective [3][4][5]. The chemical composition design ideas of ULCB steel is a low carbon equivalent with additions of micro-alloying elements including…”
Section: Introductionmentioning
confidence: 99%
“…Steel for those structures needs to have superior comprehensive properties, such as high strength, low-temperature impact toughness, seawater corrosion resistance, and good field weldability [2]. Studies have shown that a new type of ultra-low carbon bainite (ULCB) steel can meet those requirements of excellent comprehensive properties and more cost-effective [3][4][5]. The chemical composition design ideas of ULCB steel is a low carbon equivalent with additions of micro-alloying elements including…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prepared coatings are modified via LMM technology to improve their chemical and mechanical properties. The LMM treatment allows the pre-positioned coating to remelt and bond with the substrate, significantly improving its film-base bonding and densification [18][19][20][21]. Numerous studies have indicated that laser power, scanning speed, and offset are the main process parameters affecting the quality of cladding coatings [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Laser cladding is an advanced surface modi cation technique, and the cladding material and the base material surface melt at the same time, so the cladding layer and the substrate combine metallurgically. It is widely used in agricultural machinery and product performance improvement and repair, etc., because of the high density of laser energy, fast heating, and the advantages of small deformation, surface coating often alters or improves the performances of materials [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%